Elevated shear rate-induced by exercise increases eNOS ser1177 but not PECAM-1 Tyr713 phosphorylation in human conduit artery endothelial cells. Issue 4 (3rd April 2023) - Tryfonos, Andrea; Rasoul, Debar; Sadler, Daniel; Shelley, James; Mills, Joseph; Green, Daniel J.; Dawson, Ellen A.; Cocks, Matthew
ABSTRACT: Although evidence demonstrates the fundamental role of shear stress in vascular health, predominantly through the release of nitric oxide (NO), the mechanisms by which endothelial cells (EC)s sense and transduce shear are poorly understood. In cultured ECs tyrosine phosphorylation of PECAM-1 has been shown to activate eNOS in response to shear stress. However, in the human skeletal muscle microcirculation PECAM-1 was not activated in response to exercise or passive leg movement. Given this contradiction, this study aimed to assess the effect of exercise on conduit artery PECAM-1 and eNOS activation in humans. Eleven males were randomised to two groups; 30 min of handgrip exercise ( n = 6), or a time-control group ( n = 5). Protein content of eNOS and PECAM-1, alongside eNOS Ser 1177 and PECAM-1 Tyr 713 phosphorylation were assessed in ECs obtained from the radial artery pre- and post-intervention. Handgrip exercise resulted in a 5-fold increase in mean shear rate in the exercise group, with no change in the control group (group*time, P < 0.001). There was a 54% increase in eNOS Ser 1177 phosphorylation in the exercise group, when compared to control group (group*time, P = 0.016), but no change was reported in PECAM-1 Tyr 713 phosphorylation in either group (group*time, P > 0.05). eNOS and PECAM-1 protein content were unchanged (group*time, P > 0.05). Our data show that exercise-induced elevations in conduit artery shear rate increase eNOS Ser 1177 phosphorylation but not PECAM-1 Tyr 713 phosphorylation. This suggests PECAM-1 phosphorylation may not be involved in the vascular response to acute but prolonged elevations in exercise-induced shear rate in conduit arteries of healthy, active men.